2010
DOI: 10.1038/jhg.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

The association of glutathione-S-transferase gene polymorphisms (GSTM1, GSTT1, GSTP1) with idiopathic male infertility

Abstract: The effects of the GST genes (GSTM1, GSTT1 and GSTP1) on male factor infertility have not been well elucidated. A casecontrol study was performed to investigate the association between functionally important polymorphisms in GST genes and idiopathic male infertility. The study group consisted of 166 men suffering from idiopathic oligoasthenoteratozoospermia (OAT) and an equal number of age-matched healthy fertile male controls. Genomic DNA extracted from the peripheral blood, was analyzed by polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 38 publications
2
55
1
4
Order By: Relevance
“…Likewise, two more studies in the latter relation have been performed in Iran. The first, performed by Safarinejad et al, had surprising and unexpected results [22], but the second one, performed by Salehi et al, showed a correlation between idiopathic male infertility and GSTT1 and GSTM1 null deletions in men from Northern Iran [23]. Contrary to the study by Safarinejad et al we found no individual with hetero-or homozygote genotypes in codon 105 of GSTP1 (GSTP1 313 A/G and 313 G/G polymorphisms).…”
Section: Discussioncontrasting
confidence: 55%
“…Likewise, two more studies in the latter relation have been performed in Iran. The first, performed by Safarinejad et al, had surprising and unexpected results [22], but the second one, performed by Salehi et al, showed a correlation between idiopathic male infertility and GSTT1 and GSTM1 null deletions in men from Northern Iran [23]. Contrary to the study by Safarinejad et al we found no individual with hetero-or homozygote genotypes in codon 105 of GSTP1 (GSTP1 313 A/G and 313 G/G polymorphisms).…”
Section: Discussioncontrasting
confidence: 55%
“…Two other studies found that, the GSTP1 Ile/Ile genotype has been positively associated with PCa. 22,36 Mao et al examined the possible effect modification by the GSTP1 polymorphism on smoking and PCa. They found that in individuals with the Ile/Ile genotype, smoking was strongly associated with an increased risk of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of selected studies are summarized in Table 1. A total of 12 eligible studies met the inclusion criteria, including 11 studies for GSTM1 [14,15,[25][26][27][28][29][30][31][32][33] and 9 ones for GSTT1 [17,26,27,[29][30][31][32][33]. All the included studies were case-control studies.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%